Effect of Unsteady Magnetic Hydrodynamic on Oscillating Flow for Fractional Burgers’ Model - Nassief, Amaal Mohi (Al-Nahrain Journal of Science, 2017)
The purpose of this paper is studying the effect of magnetic hydrodynamic (MHD) of unsteady flow with fractional Burger’s model between two oscillating parallel plates. The fractional order derivative in described in the Riemann-Liouville sense. The solutions which we obtained of the velocity field and the shear stress by using Laplace transform and Fourier transform in the expression of Mittage-Lefller function. Furthermore, the influence of the parameters on the velocity field spotlighted by means of the several graphs.